2017
DOI: 10.1177/0731684417747742
|View full text |Cite
|
Sign up to set email alerts
|

A review on tribological behaviour of natural reinforced composites

Abstract: In the past, asbestos and copper were preferred as friction materials because they have good ability to dissipate heat, but have proven to be harmful to environment. Recently, more researches are focused on non-asbestos friction composite materials due to its non-toxicity and biodegradability. Despite synthetic fibre composites having eco-friendly nature, because of its cost and pollution most of the researchers show interest on natural fibre composites. Hence, there is a need to explore the analysis on the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…The characterization of mechanical properties of NFC plays a crucial role in determining their actual applicability in substitution to traditional composite materials . Models for the prediction of mechanical properties such as the ultimate tensile strength (UTS), the modulus of elasticity (MOE), or the strain of NFC are necessary to enable the adoption of these materials in engineering design …”
Section: Introductionmentioning
confidence: 99%
“…The characterization of mechanical properties of NFC plays a crucial role in determining their actual applicability in substitution to traditional composite materials . Models for the prediction of mechanical properties such as the ultimate tensile strength (UTS), the modulus of elasticity (MOE), or the strain of NFC are necessary to enable the adoption of these materials in engineering design …”
Section: Introductionmentioning
confidence: 99%
“…However, PA11 has poor wear resistance [4], which limits its widespread applications in many fields including the offshore and automotive industry for which the wear properties are the most important tribological characteristics [5][6][7]. According to the literature [4,[8][9][10][11][12][13][14], one of the most efficient methods to improve the tribological properties of polyamides consists in incorporating a small amount of nanofillers into the polymer matrix. This often leads to an improvement in the tribological properties of the nanocomposite materials due probably to the high contact surface area of the nanoparticles, which develop more interactions with the polymer matrix [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is a natural reaction of a substance that may either be mechanical or chemical [56]. One of the principal causes of material failure and damage to equipment is identified as friction and wear [57][58][59]. Manoj Panchal et al [60] reported tribological properties of boiled and unboiled eggshell particulates epoxy composites that are exposed to saline, mineral, subzero, and kerosene environments.…”
Section: Degradation Of Wear Properties Of Hybrid Polymer Compositesmentioning
confidence: 99%